Co-Existence of Civilizations in the Global Era - Hans Köchler (Glocalism: Journal of Culture, Politics and Innovation)
In the most general terms, “civilization” relates to the unique constitution of a “life-world”, defined by a coherent “worldview” (Weltanschauung) on the basis of continuity. This includes a community’s religious beliefs and metaphysical views, its social organization, value system, esthetical perceptions, etc. These factors also determine specific notions of dignity and societal behavior. Civilization in this multidimensional sense may comprise a variety of different cultures as sub-sections, mainly on the basis of different languages. In today’s global environment, the constant encounter and interaction between different – often incompatible – worldviews and value systems has an entirely new potential for conflict – with one humanity, whose members are constantly aware of their living in one “global village,” but with more than one, indeed a multitude, of competing global civilizations. Culture-driven conflicts – or conflicts where antagonists use culture as a tool of legitimation – are much more difficult to resolve or contain compared to conflicts where diverging (economic) interests are clearly defined and not hidden behind “ideals”. Values are not a field for realpolitik whereas interests are negotiable. The rapid development of technology, in tandem with the global pursuit of economic interests, has made interaction (encounter) with the “other” a structural fact of society. One of the major challenges of our time will be whether civilizations can agree on a set of meta-values on the basis of mutuality (such as tolerance, non-interference, etc.). Only this will enable them to avoid confrontation at the level of values of the first order (“material” values). This could also open the field for a new dialogue of civilizations in the spirit of Enlightenment, transcending the traditional missionary paradigm. Such a “meta-dialogue of civilizations” would also fit into a new approach of realpolitik towards issues of cultural identity.